Improving students' numeracy literacy through challenge-based stem context learning website using flipped classroom assisted by animation video - Meilina, Selva Ayu; Ardiansyah, Adi Satrio; Rahardi, Wilis (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purposes: The low PISA 2022 results show that students' numeracy literacy skills in Indonesia are still far below the international average. So, this research aims to examine the feasibility, the effectiveness, and student responses of challenge-based STEM context learning website named PythaFlip website to improve students numeracy literacy. Method: The research method used was Research and Development (RnD) with a 4D model (define, design, develop, and disseminate). In addition, data analysis was conducted quantitatively and qualitatively based on research instruments that had been distributed to teachers, students, and validators. Findings: The results showed a feasibility result of 85.475% with a very feasible criterion. The effectiveness test indicated that improvement of students numeracy literacy reached a high criterion reflected by score of , the student completion scores with KKTP of 70, the proportion of students who completed the average in posttest was above 70%, and an average pretest-posttest difference of 42.7875. In addition, student responses test results showed an average score of 90.75% with a very good criterion. Significance: Based on the results, it can be concluded that the PythaFlip website is very feasible, effective, and received very good responses so it contributes significantly to improving students numeracy literacy.